The cumulative effects of MEFV gene polymorphisms and mutations in patients with inflammatory bowel diseases - Agin, Mehmet; Atil Bisgin; Mustafa Yilmaz; Aylin Kont Ozhan; Ferid Mammadov; Gokhan Tumgor (Journal of the Pakistan Medical Association, 2020)
Objective: To determine the cumulative effects of Mediterranean fever gene polymorphisms and mutations in patients with ?nflammatory bowel diseases. Methods: The case-control study was conducted from January, 2012, to January, 2016,at Cukurova University, Turkey, and comprised patients diagnosed with inflammatory bowel diseases and followed up at the Children Gastroenterology Department. By using molecular methods, 12 Mediterranean fevergene variants most frequently observed in the country were examined in all the diagnosed cases. The results were compared with age-matched healthy population data from the Genetic Diseases Diagnosis and Treatment Centre. Data was analysed using Graph Pad Prism. Results: Of the 151 subjects, 46(30.4%) were cases and 105(69.5%) were controls. Among the cases, there were 23(50%) subjects with a mean age of 14.8±3 years who had ulcerative colitis, and 23(50%) with mean age 14.5±3.2 years who had Crohn’s disease. The mean age of the controls was 16.4±3.2 years (p=0.716). Patients with ulcerative colitishad high frequencies of C allele in D102D T>C variant, G allele in G138G A>G variant, A allele in A165A C>A variant and A allele in R202Q G>A variant. Those with Crohn’s disease frequently had wild type of R202Q G>A variant. Also, D102D T>C / R314R C>T haplotype was common at a certain level in the UC group. Conclusions: Mediterranean fever gene variant was more frequently found in cases with ulcerative colitis compared to the controls. Key Words: MEFV, IBD, FMF, Polymorphism, Children. Continuous....